The Social Media Contribution into Healthсare Practicesamong Russian Young People - BugrezovaEkaterina (Journal of Economic Sociology, 2016)
Today, in Western countries e-Health as a permanently growing process coincides with the distribution of the empowerment phenomenon. In addition, the gradual transformation of the relationship between doctors and patients is notable in Europe and America, especially among the younger generation. This could refer to the fact that young people actively use the Internet to research medical issues while strengthening their own healthcare responsibility. Taking into account the fact that Western youth have a high level of trust in online information, social media can influence important decision making by young people in terms of their health and visiting healthcare facilities. This tendency has an ambiguous impact, as there is always a chance of using questionable information, which is not approved by medical specialists. Currently, there is not enough literature showing how Russian young people use social media to get information about health and treatment. Thus, research focuses on e-Health in Russia and tries to find out the social media contribution to different healthcare practices among Russian young people. The research was conducted in two stages using quantitative and qualitative methodologies: An analysis of the secondary data (Marketing Index TNS Russia data) was performed, which supported the analysis of the primary data collected from 15 semi-structured interviews of young people aged from 16 to 29 years old who live in Moscow or the Moscow region who used the Internet as a source of information about health and medicine.